2002
DOI: 10.1152/ajplung.00437.2001
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of matrix with integrin receptors is required for optimal LPS-induced MAP kinase activation

Abstract: Exposure of macrophages to endotoxin [lipopolysaccharide (LPS)] results in a cascade of events resulting in the release of multiple inflammatory and anti-inflammatory mediators. The Toll-like receptor (TLR) 4 complex is the major receptor that mediates LPS signaling. However, there is evidence that other surface molecules may play a complementary role in the TLR-induced events. Integrin receptors are one class of receptors that have been linked to LPS signaling. This study investigates the role of macrophage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 46 publications
4
43
0
Order By: Relevance
“…Furthermore, FAK-expressing cells transfected with the FAK inhibitor FRNK produced significantly lower amounts of IL-6 upon LPS challenge. This is in line with previous results showing that LPS induced FAK phosphorylation in a murine monocytic cell line (18). We further demonstrated that other TLR ligands may also induce FAK phosphorylation at Tyr 397 and require FAK for cytokine release because comparable results have been obtained with the TLR2 ligand Pam 3 CSK 4 (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, FAK-expressing cells transfected with the FAK inhibitor FRNK produced significantly lower amounts of IL-6 upon LPS challenge. This is in line with previous results showing that LPS induced FAK phosphorylation in a murine monocytic cell line (18). We further demonstrated that other TLR ligands may also induce FAK phosphorylation at Tyr 397 and require FAK for cytokine release because comparable results have been obtained with the TLR2 ligand Pam 3 CSK 4 (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that LPS activates integrins, increasing integrin ligation and clustering, and thus triggering an "outside-in" signaling that amplifies the action of LPS. Consistent with our in vivo data, Monick et al (14) proposed the hypothesis that in vitro treatment of macrophages with LPS results in "insideout" integrin activation, and increased cellular adherence, providing integrin "outside-in" signaling to MAP kinases. Indeed, signals from integrin receptors seem to be required for optimal LPS signaling in macrophages.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the Arg-GlyAsp (RGD) motif of ECM entities that associate with integrin ␣ v ␤ 3 signaling appears to be involved in NF-B activation (12). Furthermore, in macrophages, integrins play a complementary role in LPS signaling, i.e., in the activations of MAP kinases (such as ERK and JNK), and in TNF-␣ production (13,14). These relations suggest that integrin signaling in macrophages mediates or amplifies inflammation.…”
Section: N Uclear Factor B (Nf-b) Is Transcriptional Regulatorymentioning
confidence: 99%
“…Previously, we reported that cell adhesion (integrin signaling) was required for lipopolysaccharide-induced activation of the mitogen-activated kinase (MAPK), extracellular regulated kinase (ERK), and optimal tumor necrosis factor-␣ production (31). In this study, we evaluated the role of adhesion (tissue culture plates and extracellular matrix-coated plates with collagen type I, collagen type IV, or fibronectin) on hyperoxia-induced growth arrest in macrophages.…”
mentioning
confidence: 99%